Gene therapy of the hemoglobinopathies - Kunz, Joachim; Kulozik, Andreas (HemaSphere, 2020)
Sickle cell disease and the ß-thalassemias are caused by mutations of the ß-globin gene and represent the most frequent single gene disorders worldwide. Even in European countries with a previous low frequency of these conditions the prevalence has substantially increased following large scale migration from Africa and the Middle East to Europe. The hemoglobin diseases severely limit both, life expectancy and quality of life and require either life-long supportive therapy if cure cannot be achieved by allogeneic stem cell transplantation. Strategies for ex vivo gene therapy aiming at either re-establishing normal ß-globin chain synthesis or at re-activating fetal γ-globin chain and HbF expression are currently in clinical development. The European Medicine Agency (EMA) conditionally licensed gene addition therapy based on lentiviral transduction of hematopoietic stem cells in 2019 for a selected group of patients with transfusion dependent non-ß° thalassemia major without a suitable stem cell donor. Gene therapy thus offers a relevant chance to this group of patients for whom cure has previously not been on the horizon. In this review, we discuss the potential and the challenges of gene addition and gene editing strategies for the hemoglobin diseases.
Zuerst online veröffentlicht: 11 September 2020
Gesehen am 23.06.2025